Application of ABC and EOQ Methods to Improve Control of Patented Medicine Inventory at Pharmacy A - Fole, Asrul; Kulsaputro, Januar; raodah, Raodah; Erniyani, Erniyani; Yanasim, Nurwindy (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2024)
Abstract The aim of this research is to analyze drug supply control at Pharmacy A using the Always Better Control (ABC) method to determine drug procurement priorities based on usage and cost guidelines, making it easier to share data regarding relevant matters and budgets for decision-making and separate items that are small in quantity but have great value. Economic order quantity (EOQ) was used to estimate the inventory that will be used, the existence of safety stock, and the time to reorder inventory. Data on drug supplies, drug unit prices, and drug use from January to December 2021 were collected and analyzed using Microsoft Excel. Medicines are classified into three groups based on their investment value. The results showed that group A had the highest investment value (80%) with 41 types of drugs, group B had a medium investment value (15%) with 24 types of drugs, and group C had the lowest investment value (5%) with 19 types of drugs. Group A's EOQ value varies from 9 item to 3170 items. This research recommends that Pharmacy A use the ABC and EOQ methods in managing drug supplies to make it more efficient, effective, and economical. Keywords:- Pharmacy, Inventory Control, ABC method, EOQ method